The Dynamics of Sesame (Sesamum indicum L.) Growth Type - Firmansyah Firmansyah; Taryono Taryono; Prapto Yudono (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2012)
(Sesamum indicumL.) is one of important vegetableoil cropsin theworld. Indonesian local sesame cultivars in use today still have indeterminate growth types that cause simultaneous harvest, narrow adaptability and lower yield. Stage of the research is to see dynamics growth type of sesame due to environmental change and to find morphological and biochemical selection criteria of determinate growth cultivar. This study uses a factorial completely randomized design consisting of three replications. The first factor is six cultivars of sesame, two types of determinate growth type cultivar introduced from Turkey III Det 23, III Det 36 and four indeterminate growth type cultivars Sbr 3, Sbr 4, white local and black local. The second factor is six environments that combine various combinations of temperature and several concentrations of NaCl as salinity stress. The results showed that the environment combined heat stress temperature and salinity affect growth type of sesame. Heat stress makes longer vegetative phase and salinity stress causes black local genotype changed to determinate growth type. III det 23 and III det 36 were considered as stable determinate cultivar and best used as a parent crossing in sesame breeding program.